2020
DOI: 10.2499/9780896293809_09
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of agricultural mechanization in Nepal

Abstract: Mechanization levels in Nepal, a largely agricultural country, were relatively low until a few decades ago. However, significant mechanization growth, including the adoption of tractors, has occurred since the 1990s, against a backdrop of rising rural wages, particularly for plowing, combined with growing emigration, growth in key staple crop yields, overall broad agricultural production growth, and improved market access and participation. This growth in mechanization has taken place despite the general absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The use of pump sets however increased from 10 000 in 1980 to 50 000 in 1991 since subsidy on irrigation equipment continued (Biggs et al, 2002). Financial support for tractors was also discouraged during the 1980–1985 period to limit traffic congestion in Kathmandu and Pokhara valleys (Joshi et al, 2012; Takeshima & Justice, 2020). The lack of policy efforts to support mechanisation is also reflected in the absence of formal agricultural mechanisation policies until the long‐term Agricultural Perspective Plan (APP) (1995–2015) and National Agriculture Policy (2004) were prepared and adopted (Biggs et al, 2002; Gauchan & Shrestha, 2017).…”
Section: Contextualising Agricultural Mechanisation Progress In Nepalmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of pump sets however increased from 10 000 in 1980 to 50 000 in 1991 since subsidy on irrigation equipment continued (Biggs et al, 2002). Financial support for tractors was also discouraged during the 1980–1985 period to limit traffic congestion in Kathmandu and Pokhara valleys (Joshi et al, 2012; Takeshima & Justice, 2020). The lack of policy efforts to support mechanisation is also reflected in the absence of formal agricultural mechanisation policies until the long‐term Agricultural Perspective Plan (APP) (1995–2015) and National Agriculture Policy (2004) were prepared and adopted (Biggs et al, 2002; Gauchan & Shrestha, 2017).…”
Section: Contextualising Agricultural Mechanisation Progress In Nepalmentioning
confidence: 99%
“…Private sector has played a crucial role in mechanisation (Gauchan & Shrestha, 2017), and recent government initiatives including subsidies and promotional programmes have also contributed to increasing machinery access and exposure. The duration between the 1990s and 2006 experienced an uptake of tractor usage in the Terai with consistent and widespread usage in the region along with the beginning of motorised pumps usage (Takeshima & Justice, 2020). In the Terai, tractor use has helped farmers intensify production with smallholder farmers in particular relying on various service providers to access machinery (Takeshima & Justice, 2020).…”
Section: Contextualising Agricultural Mechanisation Progress In Nepalmentioning
confidence: 99%
See 1 more Smart Citation
“…Such efforts need to be promoted on a larger scale as well-functioning custom hiring centres can keep the rental rates for machinery services in check 4 . Studies in other south Asian countries found a rise in the use of the tractor and consequent increase in productivity through the spread of custom hiring services (Takeshima, 2016; 2017; Yang et al, 2013). Similar studies in India, mostly done in the context of Punjab, show that cooperative use of machinery and custom hiring have resulted in significant gain in farm productivity and incomes of small and marginal farmers as they offset high fixed cost on purchase and maintenance of heavy power-driven machinery (Satyasai & Balnarayana, 2018; Singh, 2018; Singh et al, 2013; Sidhu & Vatta 2012).…”
Section: Summing Up and Agenda For Further Researchmentioning
confidence: 99%
“…China has experienced a successful transition from farms investing in large tractors and combines to a viable model of a cluster of dynamic farms providing service of machines to a wider group of farmers across regions. In Nepal the impressive growth in the use of tractors is led by private operators without much support from the government (Takeshima 2016; 2017). Bhattarai et al (2018), have maintained that despite numerous small size farms, in India tractor ownership is led by the motive to expand farm size.…”
Section: Introductionmentioning
confidence: 99%